Influences of physical training on intellectual working capacity and psychoemotional stability of students depending on specificity of professional work. - Gumenniy V. (Kharkov National Pedagogical University, 2011)
Influence of physical training on intellectual working capacity and psychoemotional stability of students depending on specificity of the future professional work by means of proof test of Anfimova is considered. Students of the Kremenchug national university who were engaged have taken part in research. Positive influence of employment on physical training on intellectual working capacity is established. It is recommended to consider and plan physical training of students, as an obligatory component of the general teaching and educational process for increase of level of mastering of general-theoretical and special subjects.